Factors associated with retinopathy of prematurity ophthalmology workload. (November 2018) - Jacob, Jack; Matrix, Zinnia; Skopec, Debra; Ticho, Benjamin; Arnold, Robert
Abstract Objective This article reports on retinopathy of prematurity (ROP) workload in the NICU related to severity of disease, gestational age at discharge, and practice variation. Study design Data analysis on 1771 patients ≤ 30 weeks of gestation at birth from a de-identified data set of 13 NICUs. Results There was a positive relationship between the severity of ROP and (1) the number of exams per patient, (2) the severity of ROP, and (3) postmenstrual age at discharge. The progression between the stages of ROP added to exam workload and postmenstrual age at NICU discharge. The addition of plus disease did not increase the exam burden. There was significant practice variation in the number of exams performed independent of ROP severity. Conclusion The progression of the severity of ROP independent of plus disease, and practice variations both contribute to ROP workload. Addressing these factors could decrease ROP workload without compromising American Academy of Pediatrics (AAP) guidelines.